Mothers' responsibility as transmitters of gendered moral rationalities: working-class Palestinian mothers living in Israel. Issue 4 (19th May 2021) - Athamneh, Sinyal; Benjamin, Orly
Abstract: Gendered moral rationalities (GMRs) have been proposed as a means of grounding mothers' employment-related choices in the structural, policy, and social support contexts of their maternal routines. This article analyzes a form of GMR that is anchored in the class-ethno-national position of mothers and comprises a manifestation of their maternal responsibility toward their daughters' futures. By focusing on this form of parenting among working-class parents, we are bridging a gap in the scholarship, which has overlooked the salience of the intergenerational transmission of GMRs. Based on the analysis of semistructured interviews with 20 working-class Palestinian mothers living in poverty in Israel, we found that their responsibility for their daughters' future reflects both the struggle to resist early marriage and prioritize education and the struggle to encourage a model of market citizenship. These struggles reshape mothers' own GMRs and their attempts to transmit these values to their daughters.